Opening statement at the ILRI-World Bank high-level livestock strategy consultation - Nabarro, D. (International Livestock Research Institute, 2012)
Presented by David Nabarro, special representative of the UN Secretary General for food security and nutrition, at the ILRI-World Bank high-level consultation on the global livestock agenda by 2020, Nairobi, 12-13 March 2012.